Multi-Cloud Architecture and Governance : Leverage Azure, AWS, GCP, and VMware vSphere to build effective multi-cloud solutions /: Leverage Azure, AWS, GCP, and VMware vSphere to build effective multi-cloud solutions. (2020) - Mulder, Jeroen
No abstract available